Strategi Marketing Mix UMKM Kota Bekasi Pada Layanan Delivery Food Online - Sarasati, Fitri; Abadi, Mansurni; Putri Kussanti, Devy; Yudha Erlangga, Christopher (LPPM Universitas Bina Sarana Informatika, 2023)
In its implementation, companies providing online food delivery services serve not only as mere delivery service providers. Beyond that, particularly for Micro, Small, and Medium Enterprises (MSMEs), this service serves as a platform that offers opportunities for small and medium-scale culinary entrepreneurs to reach a wider audience in introducing and marketing their food products or cuisines. The utilization of the marketing mix by Micro, Small, and Medium Enterprise (MSME) operators enables their culinary products to become widely recognized due to the convenience of ordering culinary products through online food delivery services. The data analysis method employed is qualitative descriptive with non-participant observation data collection techniques, where the researcher obtains primary data and secondary data through short interviews and review of various literary sources. The research findings have the potential to contribute knowledge to Micro, Small, and Medium Enterprises (MSMEs) by providing insights into marketing strategies that can be adopted by MSMEs to advance their businesses.